2003
DOI: 10.1016/s0014-5793(03)00209-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing by adenovirus‐delivered siRNA

Abstract: RNA interference is the process that double-stranded RNA induces the homology-dependent degradation of cognate mRNA mediated by 21^23 nucleotide short interfering RNA (siRNA). Here, we describe a simple virus vector for e⁄cient delivery of siRNA into mammalian cells utilizing the well-de¢ned H1-RNA promoter and conventional adenovirus. In this pilot study, p53 was targeted by this vector. Our results demonstrate e⁄cient and speci¢c knock-down of p53 in breast cancer MCF-7 and lung carcinoma A549 cells and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
107
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(107 citation statements)
references
References 20 publications
0
107
0
Order By: Relevance
“…36,37 To facilitate the application of siRNA in cancer gene therapy, it is necessary to develop improved approaches for efficient introduction of siRNA into target cells. 38,39 Viral vectors are efficient transgene-carrying systems, and previous studies have shown the antitumor ability of viral vectors in vitro and in vivo by using replication-deficient adenovirus. 39,41 Recombinant adenovirus is valuable particularly for transgene expression in hard-to-transfect cells and has been used widely in clinical and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 To facilitate the application of siRNA in cancer gene therapy, it is necessary to develop improved approaches for efficient introduction of siRNA into target cells. 38,39 Viral vectors are efficient transgene-carrying systems, and previous studies have shown the antitumor ability of viral vectors in vitro and in vivo by using replication-deficient adenovirus. 39,41 Recombinant adenovirus is valuable particularly for transgene expression in hard-to-transfect cells and has been used widely in clinical and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoviral vectors are widely used both in cells and in vivo; however, their inability to integrate into the genome has proved advantageous in terms of safety but at the cost of inefficient long-term gene silencing. [83][84][85][86][87][88][89] However, other disadvantages of using adenovirus for gene therapy are well known, including high immunogenicity and proinflammatory effects. In contrast, the adenovirus-associated viruses have been more effective in 92 Hydrodynamic injections of siRNAs alone or in conjunction with reporter constructs have led to the silencing of endogenous genes in various animal tissues, which include liver, spleen, lung, kidney and pancreas.…”
Section: Rnai Deliverymentioning
confidence: 99%
“…Then, we employed the newly developed adenovirus-delivered small interfering RNA (siRNA) technique (24) to study the effects of knockdown of c-Met on hepatocellular carcinoma cell growth in vitro and in vivo.…”
mentioning
confidence: 99%